Labor Market Impacts of States Issuing of Driving Licenses to Undocumented Immigrants - Catalina Amuedo-Dorantes; Esther Arenas-Arroyo; Almudena Sevilla (Institute of Labor Economics (IZA), 2018)
Twelve U.S. states, plus the District of Columbia, have recently enacted measures granting undocumented immigrants access to driving licenses. We exploit the state and temporal variation in the issuing of state driving licenses to undocumented immigrants to estimate its impact on these population's employment outcomes. Using 2013 through 2017 data from the monthly Current Population Survey and its Outgoing Rotation Groups, we show that likely undocumented women increase their labor supply in response to the availability of driver licenses. Their work propensity rises by 4.2 percentage points, aligning it to that of their male counterparts. In addition, those at work raise their weekly hours of work by 4 percent. Overall, their real hourly wages drop by 3 percent. We find no similar impacts among likely undocumented men –a result consistent with a standard labor supply model predicting a greater response from individuals with a larger elasticity. Additionally, we find no apparent impacts on the labor supply and wages of similarly skilled Hispanic native-born women. At a time when anti-immigrant sentiments are at an all-time high, understanding how these policies impact targeted groups and similarly skilled native populations is crucial for maintaining an informed immigration policy debate.
Keywords: I38; J15; J22; K37; 330; driver licenses; undocumented immigrants; labor market impacts; United States